The Impact of CO2 Concentration on Indoor Air Quality in Various Schools and Colleges in Baniwaleed City - Ghanem, Masood; Shahub, Lubna Ahmed (Scientific Journal for Faculty of Science-Sirte University, 2023)
Indoor air pollution has been known since ancient times, but the types of indoor air pollutants differ with the presence of modern buildings. Millions of people die each year as a result of the serious threat that indoor air pollution poses to human health. Numerous pollutants can cause indoor air pollution; therefore, it's crucial to identify their primary sources and concentrations and develop plans for enhancing and controlling the quality of the air indoors. Air-conditioned and tightly closed, especially since a person spends more than 80% of his day in closed environments. The current study included measuring the concentration of carbon dioxide inside some schools and colleges in Baniwaleed city to ensure air quality. Two primary schools, four secondary schools, and two colleges were selected. Measurements were taken twice, the first in November and the second in December. A HT 2000 CO2 meter was used for measurement, located in the laboratories of the Faculty of Science, Baniwaleed University, Department of Geology and Environmental Sciences. The highest reading was recorded at 2221 ppm at Sana Muhaidli School for Secondary Education in the month of December. The second highest reading recorded in the College of Engineering was 2005 ppm, and it was in the month of December as well. There were some readings within the permissible limits (less than 1000 ppm) and some readings higher than the permissible limit.